Variable Presentations of Enteric Fever, beyond Fever and Pain Abdomen: A Case Series - Somnath Maitra; Kaushik Hazra; Sunetra Roy (Journal of Clinical and Diagnostic Research, 2022)
Enteric Fever (Typhoid and Paratyphoid fever) is an illness that presents with marked pyrexia, abdominal pain and other gastrointestinal symptoms. Symptoms and complications primarily involve gut. But sometimes it involves other organ systems like heart, and brain. It thus poses a great diagnostic challenge in diagnosing these extraintestinal manifestations. The three cases depicted in this case series had unusual presentations in the form of dilated cardiomyopathy, non haemophagocytic lymphohistiocytosis (HLH) dyslipidaemia and encephalopathy. The first case is a case of reversible cardiomyopathy in a 26-year-old male presenting with fever for seven days with headache, loose motions and vomiting with audible S3 and bibasal crepitations without oedema. The patient responded to ceftriaxone and azithromycin. On echocardiography dilated cardiomyopathy was diagnosed after which treatment with ramipril and metoprolol was started. The second case was of a 30-year-old female presenting with fever, vomiting, and abdominal pain. There was hypertriglyceridaemia with normal ferritin levels. The patient responded to ceftriaxone. High Density Lipoprotein (HDL) level was low. Statin and fenofibrates were added after which the triglyceride levels came down. This was an interesting case of non-HLH dyslipidaemia which responded to therapy. The third case was of a 40-year-old female presenting with fever for six days with impairment of consciousness. Bilateral plantar responses were extensor and there was no papilledema or any cranial nerve palsy. Magnetic Resonance Imaging (MRI) Brain and Cerebrospinal Fluid (CSF) study were normal. The patient responded to ceftriaxone and dexamethasone proving beneficial effects of steroids in enteric encephalopathy. The purpose of the case series was to make clinicians aware of these uncommon presentations of a common disease so that early diagnosis and treatment with Anti Salmonella antibiotics can be initiated quickly to prevent complications.